Multiomics approaches on extremophiles and their application in the biological management of e-waste - Hualpa Cutipa, Edwin; Solórzano Acosta, Richard Andi; Landa Acuña, Daniela; Mendoza León, Janelle (John Wiley & Sons, Inc., 2024)
The latest technological advances in the current era have allowed development in the different areas and disciplines of science, leading to a series of discoveries that enhance current scientific knowledge. These advances are largely due to the rapid evolution in the manufacture of increasingly sophisticated electronic devices. However, the consumption and disposal of electronic devices generate environmental pollution problems (e-waste) in different matrices of the ecosystem, linked to an accelerated demographic growth. A variety of techniques have been used to reduce the outcome of e-waste. Bioremediation is an environmental and eco-friendly strategy based on the use of the metabolic capabilities of organisms and microorganisms. For a better application of these environmental strategies, the application of molecular strategies is proposed under a multiomic approach, which involves the global and integrated study of the molecular components resulting from the interaction of organisms and microorganisms with waste products. Therefore, the aim of this chapter is to provide details on the microbes that degrade electronic waste (e-waste) and their study under a multiomic perspective (genomics, transcriptomics, metabolomics, and proteomics).